IMPLEMENTATION OF VIRTUAL REALITY TECHNOLOGY IN VOCATIONAL LEARNING - Basuki, Andi; Churiyah, Madziatul; Arief, Mohammad; Dharma, Buyung Adi; Sakdiyyah, Dewi Ayu (International Education Trend Issues, 2023)
This study aims to produce innovative virtual reality-based works that can be used as archiving learning media. The design of this study adopts the Borg and Gall model which consists of 10 stages. As for the location of the implementation research at SMKN 1 Ngawi Department of Office Management and Business Services. The trial subjects involved 15 students in the small group trial and 50 students in the large group trial. This research activity also involved a validator expert to determine the feasibility and validity of the product being developed. The results of this research and development are learning media called V-Archives that are feasible and valid to be applied in the archiving learning process. This is based on the results of small group trials which obtained an average of 87% and large group trials obtained an average of 92%. While the results of the media expert validator and material expert obtained an average score of 90.75. So it can be concluded that V-Archive learning media can be used as an alternative learning media for archiving subjects